THE RELATIONSHIP BETWEEN PARENTS' SUPPORT WITH THE COOPERATIVE LEVEL OF PRESCHOOL AGED (3-6 YEARS) WHEN MEDICAL AND NURSING PROCEDURES PERFORMED IN MAHONI ROOM VITA INSANI HOSPITAL PEMATANGSIANTAR - Yunardi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
Children perceive hospitalization as an event that can be stressful. The main stressors in hospitalization are anxiety due to separation, loss of control, bodily injury and pain. The stressor will cause regression, refusing to cooperate or being uncooperative during the action. Cooperative or cooperation is a joint effort between individuals or groups of people to achieve one or several common goals. Parental support is the attitude, action, and acceptance of the family towards sick sufferers. The aim of the study was to determine the relationship between parental support and the cooperative level of preschool-aged children when medical and nursing procedures were carried out at the Trade Hospital of Simalungun Regency. This type of research is an analytic survey with a cross-sectional design and a qualitative approach. Sampling technique with accidental sampling. The sample is parents with preschool age children at the Trading Hospital with a total of 40 respondents. The data were analyzed using the Kendall Tau statistical test with a significance level of 95% and p (a<0.05). The results of 40 respondents showed that 62.5% provided parental support in the good category and from 40 preschoolers, 40% showed a cooperative level in the less category. The Kendall Tau test results obtained p=0.021 (a<0.05), with a contingency coefficient value of 0.355. There is a relationship between parental support and the cooperative level of preschool-age children when medical and nursing procedures are carried out at the Trade Hospital in Simalungun Regency.